Supervisory management : the art of inspiring, empowering, and developing people - Mosley, Donald C., 1932-; Pietri, Paul H.; Mosley, Donald C. (Mason, OH : Thomson/South-Western, 2011)
The path to becoming an effective supervisor begins with practical knowledge and skills. This title offers you the tools to develop your supervisory skills and management principles.
&#x000A
International ed."--Cover.
8th ed. of: Supervisory management / Donald C. Mosley, Paul H. Pietri, Donald C. Mosley, Jr.
Includes bibliographical references and index.
oif 24/06/14
Loan
Keywords: Personnel management; Industrial management; Supervision of employees